New deep-sea Paratanaoidea (Crustacea: Peracarida: Tanaidacea) from the northeastern Gulf of Mexico - Drumm, David T.; Bird, Graham J. (Zootaxa, 2016)
One new genus is erected and four new species of paratanaoidean tanaidaceans are described from deep waters in the northeastern Gulf of Mexico: one in each of the genera Collettea, Tanaella, and Pseudomacrinella, and one as a new genus in the family Anarthruridae. Keys to species in the genera Collettea, Tanaella, and the genera of the Anarthruridae are provided.